EFFECT OF ANATOMICAL AND CHEMICAL STRUCTURE IN THE PERMEABILITY OF “AMAPÁ” WOOD - Edy Eime Pereira Baraúna (CERNE, 2014)
This paper aimed to study the permeability to air and liquid, in the longitudinal direction of “amapá” wood (Brosimum parinarioides Ducke), originating from the Amazon Forest. Furthermore, the influence of anatomical and chemical characteristics in the permeability of the wood was investigated. For this study, samples were collected from three trees, in the state of Pará, Brazil, and submitted to permeability test, anatomical characterization, and chemical analyses. The permeability to the air of the “amapá” wood was estimated at 63.7.10-9 m³.[m.(N.m-2).s]-1 and to the liquid was 2.07.10-9 m³.[m.(N.m-2).s]-1. There were low correlations between air and liquid permeability and the anatomical features.